Synthesis of Copolymers Based on Benzene and Biphenyl and their Characterization by XRD and DSC - Triantou, Despina; Soulis, Spyridon (Journal of Research Updates in Polymer Science, 2012)
In this work the crystalinity and the thermal transitions of soluble and insoluble in chlorobenzene polyphenylene copolymers (synthesized by oxidative cationic polymerization) were studied. All copolymers had a degree of crystallinity between 44.6 and 66.7 %. With Differential Scanning Calorimentry (DSC) measurements it was found that the copolymers exhibited endothermic peaks in the region 268 up to 286 oC. These peaks in the case of soluble polyphenylenes were attributed to the melting of their crystallites, whereas in the case of insoluble polyphenylenes were attributed to liquid crystal transitions.